Features of adaptive changes in the heart muscle from a qualified sportsman’s, resulting from training load - Талатинник, О. А. (Slobozhanskyi Herald of Science and Sport, 2011)
The features of adaptive changes of heart muscle in athletes in modern pentathlon and triathlon training to a range of influences in the preparatory and competitive periods. Changes in the topography of the bulk electric field was observed in the ventricles of most athletes, that indicate the development of myocardial hypertrophy predominantly in the free and the lateral wall of the left ventricle. The data obtained allow to objectively evaluate, and thus control the adaptation of the heart muscle of athletes involved in modern pentathlon, preventing stress or frustration expressed by the adaptation of the system, which has a negative effect on athletic performance.